Eco-evolutionary dynamics in Pacific salmon - Carlson, S M (Nature Publishing Group, 2011)
Increasing acceptance of the idea that evolution can proceed rapidly has generated considerable interest in understanding the consequences of ongoing evolutionary change for populations, communities and ecosystems. The nascent field of ‘eco-evolutionary dynamics' considers these interactions, including reciprocal feedbacks between evolution and ecology. Empirical support for eco-evolutionary dynamics has emerged from several model systems, and we here present some possibilities for diverse and strong effects in Pacific salmon (Oncorhynchus spp.). We specifically focus on the consequences that natural selection on body size can have for salmon population dynamics, community (bear-salmon) interactions and ecosystem process (fluxes of salmon biomass between habitats). For example, we find that shifts in body size because of selection can alter fluxes across habitats by up to 11% compared with ecological (that is, numerical) effects. More generally, we show that selection within a generation can have large effects on ecological dynamics and so should be included within a complete eco-evolutionary framework.